Clinicopathological factors influencing outcome in metastatic colorectal cancer patients treated with fluoropyrimidine and bevacizumab maintenance treatment vs observation: an individual patient data meta-analysis of two phase 3 trials - Goey, KK (2017)
BACKGROUND: The CAIRO3 and AIO 0207 trials demonstrated the efficacy of fluoropyrimidine plus bevacizumab (FP+Bev) maintenance treatment in metastatic colorectal cancer (mCRC) patients. In this individual patient data meta-analysis with updated follow-up, we aim to provide more precise estimates of treatment effects and to identify subgroups that benefit most from maintenance treatment or observation. METHODS: In 871 patients, randomised to FP+Bev maintenance treatment or observation, we investigated whether treatment effect was modified by sex, age, performance status, response to induction treatment, primary tumour location, number of metastatic sites, disease stage and primary tumour resection, serum LDH, platelet count, CEA, and RAS/BRAF mutation status. Primary end point was time to second progression after reintroduction of the induction regimen (PFS2). Secondary end points were first progression-free survival (PFS1) and overall survival (OS). RESULTS: At a median follow-up of 68.5 months (IQR 54.6-87.0 months), maintenance treatment was more effective compared with observation in PFS1 (HR 0.40(95% CI 0.34-0.47)) and PFS2 (HR 0.70(0.60-0.81)). No subgroups were identified that did not benefit from maintenance treatment in PFS1 and PFS2; no clinically relevant subgroup effects were observed. Regarding OS, pooled results were not significant (HR 0.91(0.78-1.05)), and the trials showed marked heterogeneity in overall treatment effect and subgroup effects. CONCLUSIONS: FP+Bev maintenance treatment is effective in all patients, regardless of the investigated subgroups.